Computational fluid and solid mechanics :proceedings, First MIT Conference on Computational Fluid and Solid Mechanics, June 12-15, 2001 /. Volume 2 / editor, K.J. Bathe. - Bathe, Klaus-Jürgen.
Includes bibliographical references and indexes.